2018
DOI: 10.1134/s0006350918040188
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bacterial Cellulose Composites with Silver Nanoparticles

Abstract: Сибирский федеральный университет, 2 Институт биофизики СО РАН (ФИЦ КНЦ СО РАН) , 1 г. Красноярск, пр. Свободный 79, Россия; 2 г. Красноярск, Академгородок 50/50, Россия e-mail: шумилова Аннотация Композиты бактериальной целлюлозы (БЦ) [БЦ/AgNps], синтезированной в культуре штамма уксуснокислых бактерий Komagataeibacter xylinus VKPM B-12068 с наночастицами серебра получены гидротермальным методом при варьировании в реакционной среде концентрации ArNO 3. Присутствие серебра в композитах БЦ/AgNps подтверждено эл… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…It was found that 1.463 mg of Ag was incorporated into 100 cm 2 of BC-AgNPs composite when prepared using 1 mM AgNO 3 concentration. The result is comparable to those reported in previous studies with values ranging from 0.04-16.00 mg Ag per 100 cm 2 composite, using the same hydrothermal method to prepare BC-AgNPs composite (Li et al, 2015;Volova et al, 2018).…”
Section: Silver Content and Release Of Bc-agnps Compositesupporting
confidence: 89%
See 1 more Smart Citation
“…It was found that 1.463 mg of Ag was incorporated into 100 cm 2 of BC-AgNPs composite when prepared using 1 mM AgNO 3 concentration. The result is comparable to those reported in previous studies with values ranging from 0.04-16.00 mg Ag per 100 cm 2 composite, using the same hydrothermal method to prepare BC-AgNPs composite (Li et al, 2015;Volova et al, 2018).…”
Section: Silver Content and Release Of Bc-agnps Compositesupporting
confidence: 89%
“…Remarkably, the large inhibition zone of 29 ± 0.8 mm was measured for the BC-AgNPs composite, showing the susceptibility of S. aureus to the bactericidal effect of AgNPs (Figure 6b). Likewise, the effect was observed in other studies where the inhibition zones of 15 mm (Volova et al, 2018) and 9 mm (Yang et al, 2012) were shown by BC-AgNPs composites prepared by 1 mM AgNO 3 against the Gram-positive bacterium S. aureus. The different inhibition zone values may be caused by the use of different impregnation methods as well as the quantity of Ag + ions released from the BC composites (Wu et al, 2014).…”
Section: P R E S Ssupporting
confidence: 77%